Orbital Apex Syndrome in an Uncontrolled Diabetes Mellitus Patient: Case Report - Rahayu, Astriani (Jurnal Kedokteran Universitas Lampung, 2025)
Introduction: Orbital apex syndrome (OAS) is a complex neurological disorder characterized by a constellation of multiple dysfunctions of cranial nerves II, III, IV, V1, and VI, typically resulting from pathologies affecting adjacent structures, such as the orbit and paranasal sinuses. Early recognition and appropriate treatment are essential due to its potentially rapid progression and risk of permanent vision loss. Case Report: A 63-year-old male with uncontrolled diabetes mellitus, hypertension, and gout arthritis who presented with left periorbital pain, swelling, redness, followed by vision loss and ophthalmoplegia. Clinical examination showed no light perception, severe ptosis, proptosis, decreased corneal sensation, and a relative afferent pupillary defect (RAPD) in the left eye. Laboratory investigations showed leukocytosis and an elevated HbA1c (12%). A brain CT scan demonstrated opacification of the left ethmoid and sphenoid sinuses and enhancement at the left orbital apex. Based on clinical, radiologic, and laboratory findings, the patient was diagnosed with orbital apex syndrome secondary to ethmoid and sphenoid sinusitis. Discussion: The clinical presentation and imaging findings indicated orbital apex syndrome resulting from the contiguous spread of bacterial sinusitis in an immunocompromised host, such as those with uncontrolled diabetes. Uncontrolled diabetes likely contributed to the rapid progression. Early diagnosis and identification of the underlying causes are essential for initiating targeted therapy, including antibiotics and supportive care. Conclusion: OAS secondary to sinusitis should be considered in patients presenting with painful ophthalmoplegia and visual impairment, particularly those with poorly controlled diabetes. Early recognition and intervention are crucial for improving outcomes. Keyword: orbital apex syndrome, ophthalmoplegia, sinusitis, cranial neuropathy, vision loss